2022
DOI: 10.3390/nu15010032
|View full text |Cite
|
Sign up to set email alerts
|

MIND Dietary Pattern and Its Association with Cognition and Incident Dementia in the UK Biobank

Abstract: A high adherence to the Mediterranean-Dietary Approaches to Stop Hypertension Diet Intervention for Neurodegenerative Delay (MIND) has been associated with better cognition and a lower risk of dementia in some but not all studies. We measured adherence to MIND and its association with cognitive health in the UK Biobank (UKB). A MIND score was derived from 24 h diet recall questionnaires for 120,661 participants who completed at least one of seven self-administered cognitive function tests. In a subset of 78,66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In the subgroup analysis, we found that the protective effect of the MIND diet was more significant in females. This conclusion was also reported by a recent study that focused on the relationship between the MIND diet and the risk of dementia, as the result showed that MIND adherence contributed to a decrease in the risk of dementia in females but not males (31). Besides, a more significant association between adherence to the MIND diet and a decrease in mortality among olde people was reported in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…In the subgroup analysis, we found that the protective effect of the MIND diet was more significant in females. This conclusion was also reported by a recent study that focused on the relationship between the MIND diet and the risk of dementia, as the result showed that MIND adherence contributed to a decrease in the risk of dementia in females but not males (31). Besides, a more significant association between adherence to the MIND diet and a decrease in mortality among olde people was reported in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the same study suggested that long-term adherence to the MIND diet was associated with improved verbal memory later in life. A recent study within the UK Biobank showed that following the MIND diet was not associated with enhanced cognitive test scores ( 83 ). The MIND score was derived from 24 h diet recall questionnaires for 120, 661 individuals who completed at least one self-administered cognitive function test.…”
Section: Diets Beneficial For Patients With Alzheimer’s Dementiamentioning
confidence: 99%
“…Of 10 of the most comprehensive trials of cognitive effects of the Mediterranean diet reviewed by Morris et al [23], only four reported clear protective effects against cognitive decline or dementia [24][25][26][27]. Likewise, a recent evaluation of the association between adherence to the MIND (Mediterranean-Dietary Approaches to Stop Hypertension Diet Intervention for Neurodegenerative Delay) diet and cognitive health in the UK Biobank reported no association with better cognitive test scores and lower dementia risk only in women [28]. These conflicting results may be due to how Mediterranean diet consumption was measured [23].…”
Section: Introductionmentioning
confidence: 99%